Evaluation of Regulatory Governance of the National Electric Power Sector of Pakistan - Aleena khan; Wajid Islam; Rija Ahmad Abbasi (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study will try to evaluate the regulatory governance of National Electric Power Regulatory Authority (NEPRA). The authority was formed in 1997 to overcome the inefficiencies of Water and Power Development Authority (WAPDA) and Karachi Electric Supply Corporation (KESC) (now K-electric) and to improve the power sector through good regulations. Moreover, it was supposed to protect the interests of consumers, investors, and operators equally through its autonomy, professionalism, transparency, and credibility. Furthermore, it must grant licenses, determine tariffs and rates, ensure quality service, provide a feasible environment for privatization, and redress the complaints of electricity consumers. This study incorporates both qualitative and quantitative techniques. That is why, even after 23 years, the authority has not yet overcome the issues in the power industry. The study found that the lack of specialists, the lack of autonomy, and the lack of openness and accountability handicapped the government. This study has tried to highlight those problems which hinder the progress of NEPRA and suggested some policy recommendations for its improvement by granting autonomy, enhancing professionalism, a good complaint readdress mechanism, and inclusive in decision-making. This study has highlighted the most ignored prospects of energy regulations, which the authority has been missing for a long time, for enhancing the regulatory governance of energy.